2000
DOI: 10.1038/sj.bmt.1702374
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy and stem cell transplantation for patients with stage IV breast cancer without clinically evident disease: correlation of CD34+ selection to clinical outcome

Abstract: Summary:Forty-five patients with metastatic breast cancer without clinically evident disease were treated with thiotepa 750 mg/m 2 , mitoxantrone 40 mg/m 2 and carboplatin 1000 mg/m 2 followed by stem cell transplantation to determine the safety and efficacy of CD34 + selection of peripheral blood stem cells. Of these, 15 patients' (group I) stem cells were processed through Baxter Isolex 300 device for CD34 + selection, whereas 30 patients (group II) received unmanipulated stem cells. Toxicity, progression-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…A number of randomized studies comparing the hematopoietic recovery in CD34-selected vs non-selected autologous transplant found no significant delay in recovery of neutrophils or platelets in the CD34-selected recipients. 12,24,25 Our study found a median ANC recovery time of 9 days, with median time to platelet transfusion independence of 12 days, which is in agreement with previous trials. The use of the CD34-selected PBPC did not have any deleterious effect on the outpatient transplant approach in our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A number of randomized studies comparing the hematopoietic recovery in CD34-selected vs non-selected autologous transplant found no significant delay in recovery of neutrophils or platelets in the CD34-selected recipients. 12,24,25 Our study found a median ANC recovery time of 9 days, with median time to platelet transfusion independence of 12 days, which is in agreement with previous trials. The use of the CD34-selected PBPC did not have any deleterious effect on the outpatient transplant approach in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have looked at this in small groups of patients who received either CD34-selected PBPC or unmodified PBPC transplants. 24,25 In the study of Ahmed et al, 24 15 patients received CD34-selected stem cells and 30 patients received unmanipulated stem cells for stage IV breast cancer. They found no difference in the median overall and progression-free survivals.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] We observed a fast haematological engraftment in all patients after reinfusion with a median number of 5.8 × 10 6 CD34 + cells/kg in the CD34 + group and 4.5 × 10 6 in the PBPC group. In addition, the engraftment data indicate that G-CSF is not necessary after HDT when a satisfactory number of CD34 + cells are reinfused.…”
Section: Discussionmentioning
confidence: 99%